2021
DOI: 10.3390/jcm10173944
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Axial Length Is a Risk Factor for Proliferative Vitreoretinopathy Grade C in Eyes Unmodified by Surgical Invasion

Abstract: Purpose: To investigate the risk factors for the development of proliferative vitreoretinopathy grade C (PVR-C), independent of prior surgical invasion. Methods: Patients who underwent surgery for rhegmatogenous retinal detachment were prospectively registered with the Japan-Retinal Detachment Registry, organized by the Japanese Retina and Vitreous Society, between February 2016 and March 2017. Data obtained from general ophthalmic examinations performed before and at 1, 3, and 6 months after surgery were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A report on reoperation after ERM surgery based on IRIS (Intelligent Research In Sight) registry data has been published in the United States [9]. In Japan, the Japanese Retina and Vitreous Society (JRVS) conducted a nation-wide rhegmatogenous retinal detachment (RRD) registry study and reported the prognosis of RRD surgery using big data [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A report on reoperation after ERM surgery based on IRIS (Intelligent Research In Sight) registry data has been published in the United States [9]. In Japan, the Japanese Retina and Vitreous Society (JRVS) conducted a nation-wide rhegmatogenous retinal detachment (RRD) registry study and reported the prognosis of RRD surgery using big data [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%